Evaluation of maxillary arch width and palatal volume and depth in patients with maxillary impacted canine by CBCT. Issue 10 (October 2022) - Yassaei, Soghra; Safi, Yaser; Valian, Faeze; Mohammadi, Asma
Abstract: Introduction: Canines are the second most common tooth in terms of impaction. Impacted teeth can be associated with some different indices of dental arch and dentoalveolar structures. The aim of this study was to evaluate maxillary arch width as well as volume and depth of palate in patients with maxillary impacted canine by cone beam computed tomography (CBCT). Methods: In this cross-sectional study, 45 CBCT images of patients with unilateral maxillary impacted canines were examined. All patients had palatally impacted canines. Three parameters of maxillary arch width, palatal volume and palatal depth were assessed using axial and sagittal incisions on the CBCT images. Then all the measurements on the impacted side were compared with the non-impacted side. Data were entered into SPSS software and paired sample t-test and Student's t-test were used to comparison. The significance level of 0.05 was considered. Results: The maxillary arch width on the impacted side was significantly less than the normal side (P < 0.001). The mean depth of the palate was 14.86 ± 3.53 mm. There was a significant correlation between canine impaction and Palatal volume (R = 0.728 and P-value< 0.001), but no significant correlation between canine impaction and Maxillary arch width was shown (R = 0.15 and p-value = 0.326). Conclusion: The impacted canine was significantly associated with a reduction in the width of the maxillary arch on the affected side, and it made no difference if the impacted side was left or right. Also, impacted canine teeth were significantly associated with volume reduction on the affected side. Abstract : Impacted canine; Cone-beam computed tomography; Palatal volume; Maxillary arch width; Palatal depth.